Nuove considerazioni sul metodo psicanalitico freudiano e in generale sull’architettura empirico-razionale della metapsicologia - Baldini, Franco (Metapsychologica - rivista di psicanalisi freudiana, 2023)
There is a general indifference by psychologists, psychotherapists and psychoanalysts towards the issue of rational justification for their therapeutic practices. The element of suggestion by the therapist to the patient inevitably influences the formulation of constructions which accompany their analytic work, and therefore its elimination is the condition for their objectivity. The author points out the proximity of suggestion to the phenomenon of the placebo effect in medicine and pharmacology yet also understands the fundamental methodological differences between the two in relation to their respective fields of application. After exposing the inconsistency in every extra-clinical method in the field of psychology to eliminate suggestion from the treatment, the author formulates, starting from Freud’s explicit indications and with a procedure which draws on Systems Theory, an intra-clinical logical-experimental protocol to corroborate the clinical assertions. Providing psychoanalysis with this method of control is the prerequisite for the reproducibility of experiments and for the construction of a rational psychology.